2023
DOI: 10.15376/biores.18.1.1545-1553
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and lampshade design applications of PLA 3D printing materials

Abstract: The optical properties of PLA 3D printing materials and their influencing factors were considered relative to the manufacture of personalized 3D printing PLA lampshades. Rectangular PLA 3D printing specimens were designed, and their light transmittance and haze were analyzed in terms of color, layer height, and wall thickness using UV spectrophotometer. Using the preferred molding parameters for 3D printing of PLA lampshade, three lampshades were designed and completed via 3D printing model fabrication. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Meanwhile, PNCs have been fabricated with enhanced thermal and electrical conductivity, improved mechanical and thermal expansion, and increased fire retardancy for automotive, oil and gas, and other versatile applications 137–207 . Finally, it is emphasized that 3‐DPT and 4‐DPT are innovative processing technologies, presenting the future route of the manufacturing sector 208–244 …”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, PNCs have been fabricated with enhanced thermal and electrical conductivity, improved mechanical and thermal expansion, and increased fire retardancy for automotive, oil and gas, and other versatile applications 137–207 . Finally, it is emphasized that 3‐DPT and 4‐DPT are innovative processing technologies, presenting the future route of the manufacturing sector 208–244 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to improve the service life of the wooden furniture, people began to add a coating to the surface of the furniture to protect it [8,9]. Water-based coatings are widely used nowadays because of their advantages, such as the fast drying speed, environmental protection, and pollution resistance [10,11]. With the application of water-based coatings, it was found that the water-based coating has some defects.…”
Section: Introductionmentioning
confidence: 99%
“…A commonly used method to extend the service life of wooden products is to apply coatings on the surface of wood for protection [11,12]. The waterbased coatings use water as the dispersion medium, which is easier to obtain than an 2 of 20 organic solvent, greatly saving resources [13]. The water-based coatings have two major advantages: environmental friendliness and safety.…”
Section: Introductionmentioning
confidence: 99%